2006
DOI: 10.1128/jcm.02070-06
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Isolates Associated with Uncomplicated and Complicated Cystitis and Asymptomatic Bacteriuria Possess Similar Phylogenies, Virulence Genes, and O-Serogroup Profiles

Abstract: The genetic and serological characteristics of Escherichia coli isolates from patients with uncomplicated cystitis (UC), complicated cystitis (CC), and complicated asymptomatic bacteriuria (CASB) were determined. Phylogenetic group B2 was predominant in all categories. The prevalences of 14 out of 18 virulence factor genes were similar among the three categories, while pap, iha, ompT, and PAI were more frequently seen in isolates associated with UC than CC or CASB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
58
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 28 publications
6
58
0
1
Order By: Relevance
“…Comparing to researchers' results from China, geographically located closest to our country, Luo et al [29] and Cao et al [30] reported the most common phylogenetic group in the UPEC isolates was B2 and D. Our results support these findings. Phylogenetic group A, associated with commensal strains, represented 19.6% of isolates, which was higher than in some studies [31,32], suggesting that the gastrointestinal tract is the main reservoir of strains that may be able to colonize the urinary tract, in accordance with previous observations. UPEC strains encode a number of virulence genes that enable the bacteria to colonize the urinary tract and persist in the face of highly effective host defense [33].…”
Section: Discussionsupporting
confidence: 77%
“…Comparing to researchers' results from China, geographically located closest to our country, Luo et al [29] and Cao et al [30] reported the most common phylogenetic group in the UPEC isolates was B2 and D. Our results support these findings. Phylogenetic group A, associated with commensal strains, represented 19.6% of isolates, which was higher than in some studies [31,32], suggesting that the gastrointestinal tract is the main reservoir of strains that may be able to colonize the urinary tract, in accordance with previous observations. UPEC strains encode a number of virulence genes that enable the bacteria to colonize the urinary tract and persist in the face of highly effective host defense [33].…”
Section: Discussionsupporting
confidence: 77%
“…Our analysis revealed that the majority of the ABU and CA-ABU strains belonged to phylogenetic groups B2 and D. These phylogenetic groups are most commonly associated with extraintestinal pathogenic E. coli (2,23,30,39). In support of this typing, we also observed a widespread occurrence of virulence factors for ABU and CA-ABU strains.…”
Section: Discussionsupporting
confidence: 66%
“…In another study, the genotypic characterization of UPEC and CA-ABU E. coli strains demonstrated that UPEC and CA-ABU E. coli strains predominantly belonged to phylogenetic group B2 and shared virulence determinants. As expected, virulence-associated genes, such as the P-fimbrial determinant (pap), the UPEC pathogenicity island marker malX, as well as iha and ompT, were, however, more common in UPEC isolates than in CA-ABU isolates (55).…”
Section: Discussionmentioning
confidence: 95%